PENGATURAN PEMUTUSAN HUBUNGAN KERJA DALAM PERSPEKTIF KEPENTINGAN EKONOMI DAN HAK ASASI MANUSIA - Santoso, Budi (Jurnal Media Hukum, 2017)
Issue of dismissal is closely related to human rights and economics. The regulating must consider both aspects. This paper explores how the economics perspective and human rights perspective on the issue. On the economics perspective, although the neoclassical economics theory and the theory of new institutional economics have a difference in perspective on the issue, whether or not it stipulated by legislation, but both have a common view that the dismissal should not affect the company's productivity and efficiency. Meanwhile, on the human rights perspective, the worker is entitled to a fair dismissal.